2000
DOI: 10.1109/82.899629
|View full text |Cite
|
Sign up to set email alerts
|

Noise analysis of externally linear systems

Abstract: Noise analysis in externally linear time-invariant systems is complicated by the facts that noise sources may not be stationary and the relationships between the noise sources and the output are generally nonlinear. In this paper, we present a general noise analysis method which can be used to speed up repetitive noise calculations for a given system, and, most importantly, for theoretical investigations of its noise behavior, possibly leading to low-noise design techniques. A current mode syllabic companding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…signal * noise intermodulation takes place. The case of Externally-Linear-Internally-NonLinear (ELIN), time-invariant responses has been studied both theoretically and by means of measurements and simulations [30],[44],[45]. It has been confirmed that when the input signal increases considerably in strength with respect to the input DC value (for example, in class-AB operation the ratio of these two quantities can be in the range of thousands), then the noise power increases with the power of the input.…”
Section: Robustness and Electrical Properties Of Cytomimetic Circuitsmentioning
confidence: 99%
“…signal * noise intermodulation takes place. The case of Externally-Linear-Internally-NonLinear (ELIN), time-invariant responses has been studied both theoretically and by means of measurements and simulations [30],[44],[45]. It has been confirmed that when the input signal increases considerably in strength with respect to the input DC value (for example, in class-AB operation the ratio of these two quantities can be in the range of thousands), then the noise power increases with the power of the input.…”
Section: Robustness and Electrical Properties Of Cytomimetic Circuitsmentioning
confidence: 99%